A novel Halbach array electromagnetic pump for liquid metal flow: Design proposal and performance analysis. (April 2023) - Yao, Liang; Li, Xiao-Bin; Zhang, Hong-Na; Chen, Li-Xia; Li, Feng-Chen
Highlights: Propose a novel Halbach array electromagnetic pump (HA-EMP) for the first time. Carry out numerical analysis of the MHD coupling mechanism for DC-EMP. Static head and efficiency of an HA-EMP can be increased by more than 84% and 15%. Volume of an HA-EMP can be saved by more than 50%. Abstract: This paper proposes a "Halbach array electromagnetic pump for liquid metal" (HA-EMP) by applying the "Halbach ring permanent magnet array" to a direct current conductive electromagnetic pump (DC-EMP). Material selection and structure designs are carried out based on the application background of the liquid metal secondary loop in a space reactor. Performance under different flow rates, currents and duct dimensions of the electromagnetic pump are studied. The conclusions are as follows. The magnetohydrodynamic (MHD) braking effect caused by the magnetic field is responsible for the limited flow rate in DC-EMP. Increasing the magnetic flux density in the fluid facilitates a higher pressure head but also a lower flow rate. Comparing with the traditional structure electromagnetic pump (Trad-EMP), HA-EMP possesses more development potential in view of higher pressure head, smaller size and lighter weight. For the same size, the HA-EMP increases static pressure head and work efficiency by more than 84% and 15%, respectively, while the flow rate is reduced by more than 41%, at conditions of the currently studied parameter ranges. When the magnetic flux density is the same, HA-EMP can save more than 50% of volume compared to Trad-EMP. However, the end effect of the magnetic field along the flow still severely hinders its better performance and will become the next focus of optimization.